No Different Acute Effect Of Passive And Active Stretching On Hamstring Flexibility In Elderly Women - Rustanti, Marti (Poltekkes Kemenkes Surakarta, 2023)
Background: The flexibility of the hamstring muscle contributes significantly to movement and the risk of injury. Decreased hamstring flexibility increases the risk in older women with age. Stretching is the most common form of intervention to overcome this problem, but the most appropriate form of stretching for older women still requires further research. Methods: The study included 2 groups, where Group I received passive stretching treatment on the hamstring muscles while Group II received active stretching treatment on the same muscles. The subjects of this study were elderly women members of the Posyandu Elders from Tohudan Village, Colomadu District, Karanganyar Regency. Results: The results showed that there was a decrease in hamstring flexibility in older women. Passive stretching treatment has an effect on increasing hamstring muscle flexibility (p = 0.00). There was an effect of active stretching on increasing hamstring muscle flexibility (p = 0.03). There was no difference in the effect between passive stretching and active stretching on increasing hamstring muscle flexibility (p = 0.837). Conclusion: Passive stretching treatment has an effect on increasing hamstring muscle flexibility (p = 0.00). There was an effect of active stretching on increasing hamstring muscle flexibility (p = 0.03). There was no difference in the effect between passive stretching and active stretching on increasing hamstring muscle flexibility (p = 0.837). Conclusion: Based on the results of this study, it can be concluded that providing passive stretching and active stretching can both increase hamstring muscle flexibility in older women.